The Obstacles that Parents Encountered when Taking Children to Psychological Clinic in Vietnam - Nguyen Thi Dung (Randwick International of Social Science Journal, 2020)
This study aimed to explore difficulties that parents faced when bringing their children to psychological examination in Vietnam through their life stories. The research participants included 5 fathers and 3 mothers having children diagnosed with autism. A preliminary interview prior to the study and in-depth interviews were carried out with their voluntariness. To collect and analyze the data, "Life Story Interview" list was implemented, data analysis phases of interpretative phenomenology was used in this study. As a result, key problems that parents met on this tough journey so that their children could be examined were (1) financial problems, (2) tiredness, and (3) unexpected behaviors of the children. Analyses showed that despite the challenges, parents tried their best in order to know exactly the name of their children’s problem.